Impact of Endogenous Pneumococcal Hydrogen Peroxide on the Activity and Release of Pneumolysin - Bazant, Jasmin; Ott, Benjamin; Hudel, Martina; Hain, Torsten; Lucas, Rudolf; Mraheil, Mobarak Abu; Justus Liebig University Giessen (My University, 2023)
Streptococcus pneumoniae is the leading cause of community-acquired pneumonia. The pore-forming cholesterol-dependent cytolysin (CDC) pneumolysin (PLY) and the physiological metabolite hydrogen peroxide (H2O2) can greatly increase the virulence of pneumococci. Although most studies have focused on the contribution of both virulence factors to the course of pneumococcal infection, it is unknown whether or how H2O2 can affect PLY activity. Of note, S. pneumoniae exploits endogenous H2O2 as an intracellular signalling molecule to modulate the activity of several proteins. Here, we demonstrate that H2O2 negatively affects the haemolytic activity of PLY in a concentration-dependent manner. Prevention of cysteine-dependent sulfenylation upon substitution of the unique and highly conserved cysteine residue to serine in PLY significantly reduces the toxin’s susceptibility to H2O2 treatment and completely abolishes the ability of DTT to activate PLY. We also detect a clear gradual correlation between endogenous H2O2 generation and PLY release, with decreased H2O2 production causing a decline in the release of PLY. Comparative transcriptome sequencing analysis of the wild-type S. pneumoniae strain and three mutants impaired in H2O2 production indicates enhanced expression of several genes involved in peptidoglycan (PG) synthesis and in the production of choline-binding proteins (CPBs). One explanation for the impact of H2O2 on PLY release is the observed upregulation of the PG bridge formation alanyltransferases MurM and MurN, which evidentially negatively affect the PLY release. Our findings shed light on the significance of endogenous pneumococcal H2O2 in controlling PLY activity and release.
Keywords: ddc:570